Stratospheric aerosol effects from Soufriere Volcano as measured by the SAGE satellite system - Mccormick, M. P.; Kent, G. S.; Yue, G. K.; Cunnold, D. M. (1982)
During its April 1979 eruption series, Soufriere Volcano produced two major stratospheric plumes that the SAGE (Stratospheric Aerosol and Gas Experiment) satellite system tracked to West Africa and the North Atlantic Ocean. The total mass of these plumes, whose movement and dispersion are in agreement with those deduced from meteorological data and dispersion theory, was less than 0.5 percent of the global stratospheric aerosol burden; no significant temperature or climate perturbation is therefore expected.